Processing technologies for gold-telluride ores - Zhang, Jian; Zhang, Y.; Richmond, William; Wang, H. (Springer, 2010)
Gold telluride ores are important gold refractory ores due to the presence of sulfides and other gangue materials. The classification and main physical properties of gold telluride ores were described, and possible treatment methods including flotation, leaching, and oxidation were reviewed. The results show that flotation procedures are much easier for gold tellurides compared to other refractory gold-bearing ores. For the conventional cyanide leaching process, pretreatment such as oxidation is required to achieve high gold recovery. Roasting is a relatively simple but not environment-friendly method; bio-oxidation technology seems to be more suitable for the oxidation of flotation concentrate. Other treatment methods involve cyanide leaching, thiourea leaching, ammoniacal thiosulfate leaching, carbon-in-pulp, andresin-in-pulp, all of which are less commonly utilized.